Cytotoxicity studies of tetraprelyltoluquinone, a prenilated hydroquinone from Garcina cowa Roxb on H-460, MCF-7 and DU-145 - Wahyuni, Fatma Sri; Stanslas, Johnson; Lajis, Nordin; Hamidi, Dachriyanus (Innovare Academic Sciences, 2015)
Objective: The aim of the present study was to examine the cytotoxicity of a new ring-reduced tetra prenyltoluquinone (TPTQ), [2E,6E,10E]-(+)-4b-hydroxy-3-methyl-5b-(3,7,11,15-tetramethyl-2,6,10,14-hexadecatetraenyl-2-cyclohexen-1-one against H-460, MCF-7 and DU-145 cell lines. Methods: Different concentrations of TPTQ were subjected to cytotoxicity study by using MTT method and calculate the percentage of cell viability. Results: The results of this study showed that this compound has IC50 value 16.3 ± 3.0 µM in H-460 cancer cell lines without any activities towards another two type of cell lines. Conclusion: TPTQ had selective activity against H-460 cancer cell lines.